Folias de Reis: between clippings and collages (Revista Apotheke, 2024)
This visual essay is the result of a research process carried out between 2004 and 2008 in the Visual Arts course at the Federal University of Uberlândia, whose theme is linked to the figure of clowns present in the Folias de Reis de Carmo do Rio Claro - Minas Gerais. In the meantime, a record of a poetic-visual work based on the technique of cutting and collages is presented, in which the representations of the clowns are constructed interspersed between arabesque lines, chita textiles, floral elements, musical instruments and other props present in these manifestations of religiosity. popular. Context of different crossings between materialities, procedures and supports expand until the sublime moment of encounter between the artistic works and their source of imagery-cultural reference, the Folia de Reis.
Keywords: visual essay; artistic creation process; poetic experience; Folias de Reis